2009
DOI: 10.1016/j.crte.2009.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Fractures, hydrothermal alterations and permeability in the Soultz Enhanced Geothermal System

Abstract: Borehole studies of the Soultz-sous-Fore ˆts granite are dedicated to deep geothermics. The hydraulic properties of the reservoir are mainly controlled by the occurrence of some altered cataclastic shear zones showing a low natural permeability characterized by the occurrence of brines. Those zones show a fracture cluster organisation with sealed fractures of various types (post-filled joints, sheared fractures, veins). The main hydrothermal deposits observed within the permeable zones are geodic quartz, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 30 publications
1
47
1
Order By: Relevance
“…Ledésert et al 1996;Aquilina et al 1997) and as a heat-exchanger, the majority of studies aimed at assessing or quantifying the permeability at the geothermal sites at Soultz-sous-Forêts and Rittershoffen, for example, have focussed on the granite basement (e.g. Genter and Traineau 1996;Shapiro et al 1999;Sausse et al 2006;Dezayes et al 2010;Ledésert et al 2010;Vogt et al 2012a, b;Vidal et al 2017). Few studies, especially laboratory studies that offer values of porosity and permeability, have targeted the overlying Permo-Triassic sedimentary units (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ledésert et al 1996;Aquilina et al 1997) and as a heat-exchanger, the majority of studies aimed at assessing or quantifying the permeability at the geothermal sites at Soultz-sous-Forêts and Rittershoffen, for example, have focussed on the granite basement (e.g. Genter and Traineau 1996;Shapiro et al 1999;Sausse et al 2006;Dezayes et al 2010;Ledésert et al 2010;Vogt et al 2012a, b;Vidal et al 2017). Few studies, especially laboratory studies that offer values of porosity and permeability, have targeted the overlying Permo-Triassic sedimentary units (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to investigate preferential channels for natural hydrothermal circulation, their contribution to well permeability, and their history and evolution in terms of secondary mineralogy. Based on geothermal development in the URG, the permeability of the granitic reservoir appears to be controlled by fractured zones that act as preferential pathways for natural hydrothermal circulation Ledésert et al 2010Ledésert et al , 1993Rotstein et al 2006;Sausse et al 2010;Sausse and Genter 2005;Villemin and Bergerat 1987). A large number of studies have tried to characterize permeability, fracture geometry, and hydrogeological systems for geothermal applications or nuclear waste storage, whereas a few studies have addressed the hydrogeology of the deep-seated crystalline rocks (Ishibashi et al 2016;Moreno and Neretnieks 1993;Stober and Bucher 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dots represent the granite while inclined grey and white layers correspond to the sedimentary cover. After Ledésert et al (2010). (2008) and Hébert et al (2011).…”
Section: Geological Contextmentioning
confidence: 98%
“…At Soultz, thorough petrographic studies of the fracture network (Dubois et al, 2000;Genter et al, 1995;Hébert et al, 2010Hébert et al, , 2011Ledésert et al, 1999Ledésert et al, , 2009Ledésert et al, , 2010 have shown that more than 90% of the fractures are sealed by minerals that precipitated because of natural fluid flow. K-Ar dating of illite (K-bearing clay mineral) found in a fractured and altered zone located at 2200 m in the Soultz granite (Bartier et al, 2008) indicate at least two episodic illitization at 63 Ma or slightly more for the coarsest particles and at 18 Ma or slightly less for the smallest.…”
Section: Development Of the Soultz Egsmentioning
confidence: 99%
See 1 more Smart Citation